Decentralized Finance as a Digital Financial System in Maqasid Sharia Perspective - Widiyanti, Marlina; Wusqo, Urwatul; Kadir, Syahruddin (IKONOMIKA, 2024)
The rise of innovation and technological development has triggered a revolution in the financial sector with a new 'non-centralized' system. The purpose of this study is to comprehend the idea of decentralized finance and pinpoint its advantages. Using literature sources, this study employs a qualitative descriptive methodology. Books, periodicals, and other publications are examples of secondary data. According to the study's findings, DeFi has five maslahah: 1) Maintain religion (hifzu al-din); 2) Preserve the soul (hifzu an-nafs); 3) Preserve offspring (hifzu al-nasl); 4) Preserve the intellect (hifzu al-'aql); and 5) Preserve property (hifzu al-maal). These principles align with technology and the development aspects of the era of Society 5.0. Consequently, it is advised that the government implement a regulation utilizing blockchain technology in the banking industry.